LOW TEMPERATURE CARBON DIOXIDE FLOODING IN HIGH TEMPERATURE RESERVOIRS - HAMDI, ZAKARIA (2017)
CO2 injection has been used for several decades as a successful recovery method in enhanced oil recovery. The main impact of CO2 is on lowering minimum miscibility pressure. However, the unfavorable mobility of CO2 compare to other tertiary mechanisms forces us to use CO2 with other methods such as water alternating gas to minimize this effect. Low temperature CO2 injection may cover the role of the water and other fluids in this process. The injection of CO2 at low temperatures opens a unique opportunity to investigate the potential for usage of low temperature CO2 as an enhanced oil recovery method. In this study, the effect of low temperature injection on minimum miscibility pressure is evaluated in a high temperature system. Usage of low temperature CO2 may decrease the minimum miscibility pressure, but since the viscosity of oil increases by decrease of the temperature, the oil recovery must be monitored along with changes in minimum miscibility pressure. Additionally, in CO2 injection at low temperature systems, a series of complex phase behavior may happen. Some of these phases are major factors for oil recovery. Therefore, the effect of phases inside the system must be investigated closely in microscale as well as macroscale. Finally, since the proposed method must be feasible for field scale implementation, the proposed method (i.e. low temperature CO2 injection) needs to be compared with other tertiary recovery methods to verify its effectiveness against other recovery methods. If proven effective, the usage of CO2 would add its advantage along with its current huge economic and environmental advantages against other enhanced oil recovery (EOR) methods.